Audience Responses to Newspaper Coverage of Floods in China: Victims Versus Onlookers - Ning, Li; Ting, Su Hie (Penerbit Universiti Sains Malaysia (USM Press), 2026)
Framing studies show a favourable portrayal of the China government’s flood management but how does newspaper coverage shape readers’ perceptions and attitudes towards floods? This research examines the audience responses to newspaper coverage of floods in China from the perspective of victims and onlookers. The specific objectives of the study are to: (1) determine the themes in the participants’ narratives about flood incidents and the association of these themes with the affective, behavioural, and cognitive aspects; and (2) compare the responses of victims and onlookers to flood news reporting. The study involved semi-structured interviews with 20 participants living in China (13 flood victims and 7 onlookers who did not experience flood). The deductive thematic analysis of the interview transcripts was guided by the affective-behaviour-cognitive (ABC) model of attitudes. The interviews revealed the emotional reactions of flood victims versus the cognitive engagement of onlookers. Flood victims looked to and trusted the national newspaper, People’s Daily, for flood-related news while onlookers preferred regional newspapers for more localised coverage and critical content. The findings show that both victims and onlookers are aware of media control and the role of big data algorithms to push selected national news but still trust newspapers over social media as sources of information during flood crises.